Infection Related Glomerulonephritis Associated with Staphylococcus epidermidis in the Absence of Prosthetic Material - Samer Mohandes; Eshetu Obole; Anjali Satoskar; Hari Polenakovik (Case Reports in Nephrology)
We report a case of a 72-year-old diabetic male who developed infection-related glomerulonephritis (IRGN) in the setting of severe Staphylococcus epidermidis infection. He required renal replacement therapy for 6 weeks, but had full recovery of his kidney function with aggressive treatment of the infection. While this pathogen has been previously implicated as the cause of shunt nephritis, it is exceptionally rare to be associated with IRGN in the absence of a shunt or other prosthetic material.